(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The integration of Machine Learning (ML) in personalized nutrition represents a transformative approach to tailoring dietary recommendations based on individual health needs and preferences. This study investigates the application of ML algorithms to analyze dietary patterns and predict health outcomes, aiming to enhance the efficacy of personalized nutrition strategies. Utilizing a diverse dataset comprising dietary intake records, health metrics, and demographic information, various ML models—including clustering algorithms, classification techniques, and regression methods—are employed to identify patterns and associations between diet and health outcomes. Key models such as Support Vector Machines (SVM), Decision Trees, and Neural Networks are evaluated for their ability to predict nutritional needs and potential health risks. The study also explores the effectiveness of ensemble methods and feature selection techniques in improving model accuracy. Results demonstrate that ML-driven approaches can significantly improve the precision of dietary recommendations by considering individual variations in metabolism, lifestyle, and genetic factors. The findings suggest that incorporating ML into nutritional assessments can lead to more personalized and actionable dietary advice, ultimately supporting better health management and disease prevention. This research highlights the potential of ML to revolutionize personalized nutrition and advocates for further exploration and refinement of these technologies to optimize health outcomes.